Pendidikan Kesehatan, Deteksi Dini Depresi Dan Implementasi Hipnotis 5 Jari Untuk Menurunkan Depresi Pada Lansia Di UPT Pelayanan Sosial Tresna Werdha Blitar Di Tulungagung - wijaya, endah; Prihananto, Dhian Ika; Aizah, Siti; Ariyanti, Ariyanti; Oktaviana, Emmy; Andini, Fitri Nur (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Depression is mood disorder which is indicated by symptoms including feeling sad, confused, hopelessness, reduced concentration and thinking about suicide. One of the non-pharmacological treatments to reduce the level of depression in the elderly is 5 finger hypnosis therapy. The aim of this section is to provide health education about depression, early detection of depression and therapy 5 finger hypnosis to reduce depression in the elderly. The activities are health education, early detection of depression and performing 5 finger hypnosis. The results of examining the level of depression before treatmentsfor in 30 elderly people who experienced depression, none or at least 5 elderly people (17%), 7 elderly people with mild depression (23%), 18 elderly people with moderate depression (60 %) and none experienced major depression (0%). The results of examining the level of depression in the elderly after using 5 finger hypnosis showed that of the 30 elderly who experienced depression, none or at least 14 elderly (46%), 11 elderly who experienced mild depression (37%), 5 elderly who experienced moderate depression. (17%) and elderly with no major depression (0%). The conclusion is that 5 finger hypnosis is effective in reducing the level of depression in the elderly.